Current recommendations on optic neuritis = Aktuelle Empfehlungen zur Optikusneuritis - Beisse, Flemming; Beisse, Christina (Klinische Monatsblätter für Augenheilkunde, 2020)
Background Optic neuritis is a special challenge to the ophthalmologist. It is a relatively frequent condition but difficult to seize morphologically. It has neurological implications and is subject matter of recent trials. Methods Selective literature search including the authorsʼ professional experience. Results Practical aids for the ophthalmological management of optic neuritis are derived from the best available evidence and the recent literature is discussed. Conclusions The present paper provides evidence-based recommendations for a safe handling of optic neuritis as well as information on current issues.
Gesehen am 14.01.2021